Stylophora pistillata: Effect of Fragment Size and Water Depth on Growth Rate of Transplanted Coral - Kadek Andina Widiastuti; Luh Putu Eswaryanti Kusuma Yuni; Ida Ayu Astarini (Jurnal Perikanan Universitas Gadjah Mada, 2023)
Coral transplantation activities are carried out as conservation efforts to save coral reef ecosystems and the species that live and depend on these ecosystems. In its implementation, knowledge regarding effective and efficient transplantation methods is required. The aim of this research was to determine the effect of fragment size and water depth on the growth rate of transplanted Stylophora pistillata at Serangan Beach. By knowing this, coral transplantation activities can be carried out effectively. Field research was carried out from November to April 2022 using the Randomized Block Design method with two factors, namely depth variation (1 m, 3 m, and 5 m) and initial fragment sizes (3 cm, 5 cm and 7 cm). This study used 135 fragments of Stylophora pistillata. The analysis showed that the fragment sizes of 3 cm, 5 cm and 7 cm had significant differences in the rate of coral growth. However, based on the depth variation, only the depth of 1 m differed significantly from the other two depths. The best coral growth rate was observed in corals using an initial fragment size of 7 cm which was transplanted at a depth of 1 m with the highest average growth rates of 0.93 cm/month (height) and 0.79 cm/month (width). Based on the results, it was also known that the number of corals remaining at the end of the study was 265 fragments so the value of survival rate from transplantation activities was 97.78%. Maintaining environmental water conditions and carrying out maintenance and cleaning corals from algae and sedimentation needs to be carried out intensively to maintain the survival rate on Serangan Beach.